Kelimpahan dan Keragaman Kapang pada Sampel Tanah di Sekitar Kawasan Taman Nasional Gunung Ciremai, Jawa Barat - Ilyas, Muhammad (Perhimpunan Biologi Indonesia, 2009)
ABSTRACTThe Abundance and Diversity of Fungi Inhabiting Soil Samples from Mount Ciremai NationalPark, West Java. A study on isolation and identification of mould inhabiting soil samples hasbeen conducted. The objective of the study was to isolate and identify mould inhabiting soilsamples from Mount Ciremai National Park, West Java. The mould isolation was based onsample dillution method with Rose Bengal Cloramphenicol Agar mould isolation media. Theabundance of mould counted by measuring the average Colony Forming Unit (CFU)/ml of allmould colonies which growth on isolation media by Total Plate Count (TPC) method. Thediversity of isolated mould was identified based on morphological character. The result showedthat the average of mould colonies between 8,5x103-11,3x104 CFU/ml. The result of mouldidentification showed that nine mould generas are Aspergillus (6 species), Chaetomium (2species), Eupenicillium, Gliocladium, Mucor, Penicillium (6 species), Rhizopus, Trichoderma(2 species), and two groups of unidentified sterile mould.Key words: abundance, diversity, mould, soil samples, Mount Ciremai National Park